2007
DOI: 10.1021/om7007925
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of the First N-Aryl Acyclic Diaminocarbene and Its Transition-Metal Complexes

Abstract: The first acyclic diaminocarbene (ADC) featuring N-aryl groups, as well as two complexes containing this ligand, (ADC)RhCl(1,5-cis,cis-cyclooctadiene) and (ADC)RhCl(CO)2, were synthesized and characterized. Insight into controlling conformational diversity in acyclic diaminocarbenes with N-aryl groups through judicious N substitution was also explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…It proved possible to perform single‐crystal X‐ray diffraction studies on 26 , 29 , 30 and 32 – 35 . To complement these results, we also determined the crystal structures of the selenoureas 36 – 38 , which we respectively prepared from the stable ADACs ( i Pr 2 N)C(PipMe 2 )7e and (RNMe) 2 C [R=mesityl (Mes), 2,6‐diisopropylphenyl (Dipp); Scheme ] 7a,b…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It proved possible to perform single‐crystal X‐ray diffraction studies on 26 , 29 , 30 and 32 – 35 . To complement these results, we also determined the crystal structures of the selenoureas 36 – 38 , which we respectively prepared from the stable ADACs ( i Pr 2 N)C(PipMe 2 )7e and (RNMe) 2 C [R=mesityl (Mes), 2,6‐diisopropylphenyl (Dipp); Scheme ] 7a,b…”
Section: Resultsmentioning
confidence: 99%
“…This can be rationalised by the results of DFT calculations, which showed that ADAC 12 has a minimum energy conformation with the 2,2,6,6‐tetramethylpiperidino unit perpendicular to the N 2 C plane, which suppresses the π donation of this amino group and causes an unusually low LUMO energy and hence high electrophilicity. The least electrophilic ADACs known to date, according to the NMR criterion, are the isolable carbenes (ArMeN) 2 C (Ar=Mes, Dipp) reported by Bielawski and co‐workers 7a,b. The well‐known ADAC ( i Pr 2 N) 2 C reported by Alder and co‐workers6 has an intermediate electrophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…[9a] This similarity in chemical behaviour is not at all surprising because the cyclic amino group (PipMe 2 )c an be viewed as ac onformationally constrained version of the iPr 2 Ng roup. In contrast to these two isolable,b ut still highly reactive, dialkylamino-substituted acyclic carbenes,a lkyl(aryl)amino-substituted congeners (ArMeN) 2 C( Ar = mesityl, [3b] 2,6-diisopropylphenyl [15] )r eported by Bielawski and co-workersa re significantly less reactive. They show perfect thermal stabilitya tr oom temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1) [10]. The limited amount of ADC coordination chemistry that has appeared following Alder's work [11][12][13][14][15] points out some ligand properties of ADCs that could potentially provide certain advantages over NHCs: ADCs can act as stronger r-donors than NHCs [11,16], their larger N-C-N angles can place steric bulk or chiral substituents nearer to the metal center [11,12,15], and hindered rotation about the carbene C-N bonds [10,17] provides conformational flexibility [15] that could lead to ''flexible steric bulk [18]." Investigations of ADCs as ancillary ligands in catalysis have been very few [14,19,20], but they have been shown to provide comparable or better activity relative to analogous NHC systems in certain types of Pd-catalyzed coupling reactions [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of ADC coordination chemistry since Alder's work have largely utilized synthetic routes involving the free carbenes [11][12][13][14][15], which creates limitations on the types of ADCs that can be used. In contrast to imidazolium-derived NHCs [22], free ADCs are thermodynamically inclined to dimerize to enetetramines [23], although sufficient steric bulk as in A can prevent this [10].…”
Section: Introductionmentioning
confidence: 99%